A systematic review of theories, models and frameworks used for youth engagement in health research - Sanchez, Sherald; Thorburn, Rachel; Rea, Marika; Kaufman, Pamela; Schwartz, Robert; Selby, Peter; Chaiton, Michael (Health expectations : an international journal of public participation in health care and health policy, 2024)
Background Youth engagement in research, wherein youth are involved in the research beyond mere participation as human subjects, is growing and becoming more popular as an approach to research. However, systematic and deliberate theory‐building has been limited. We conducted a systematic review to identify and synthesize theories, models and frameworks that have been applied in the engagement of youth in health research, including mental health. Methods Six academic databases (MEDLINE, PsycINFO, Embase, PubMed, Scopus, CINAHL) and the grey literature were searched for relevant studies. Citation tracking was conducted through ancestry and descendancy searches. The final search was completed on 7 February 2023. Findings were summarized in a narrative synthesis informed by principles of hermeneutic analysis and interpretation. Reporting of results is in accordance with the PRISMA (Preferred Reporting Items for Systematic reviews and Meta‐Analyses) 2020 Statement. Results Of the 1156 records identified, 16 papers were included, from which we extracted named theories (n = 6), implicit theories (n = 5) and models and frameworks (n = 20) used for youth engagement in health research. We identified theories that were explicitly stated and surfaced theories that were more implicitly suggested. Models and frameworks were organized into four categories based on their principal features: power‐focused (n = 8), process‐focused (n = 7), impact‐focused (n = 3) and equity‐focused (n = 2). Few frameworks (n = 5) were empirically tested in health‐related research. Conclusions The state of theoretical development in youth engagement in research is still evolving. In this systematic review, we identified theories, models and frameworks used for youth engagement in health research. Findings from this systematic review offer a range of resources to those who seek to develop and strengthen youth engagement in their own research. Patient or Public Contribution Youth engaged as patients in the research were not involved in planning or conducting the systematic review. However, youth researchers in their early to mid‐20s led the planning, implementation and interpretation of the review. As part of subsequent work, we formed a youth advisory board to develop a youth‐led knowledge mobilization intended for an audience of youth with lived experience of being engaged as patients in research.